(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Algometers are instruments that measure actual pressure and/or pressure that causing a pressure pain threshold to be surpassed. In pressure pain threshold studies, it has been discovered that the rate at which mechanical force is applied should be steady in order to offer the maximum precision. The accuracy and composite reliability of an algometer (1000-Hz sampling rate) were tested in this study by manually applying force to a maximum force (500-Hz sampling rate). The pressure level is the lowest amount of force (pressure) that causes discomfort. The pressures threshold metre (PTM) is indeed a strength measure with a 1cm2 surface circular polymer applicator surfaces rubber disc, as well as the maximum stress measurement was examined using SEM and t-test. This device has proved beneficial in the treatment of deep muscular soreness, trigger points, fibrositis, and myalgia patches. PTM can identify arthritis activity as well as measure reduction in pain.